2004
DOI: 10.1016/j.jasms.2004.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Phenyl- and cyclopentylimino derivatization for double bond location in unsaturated C37-C40 alkenones by GC-MS

Abstract: A method for the identification of double bond locations in polyunsaturated long chain alkenones adapted to nanogram amounts as currently analyzed by gas chromatography coupled to mass spectrometry (GC-MS) has been developed. The method is based on interpretation of the electron impact mass spectra of the imino derivatives of the carbonyl groups using either cyclopentyl or phenyl substitutents. Other complementary derivatization methods such as elaidization and hydrogenation have also been used for structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
20
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 36 publications
5
20
0
Order By: Relevance
“…However, attempts to locate the positions of the double bonds based on GC-MS studies of vicinal bistrimethylsilyl ethers [8] or dimethanethiols [9] had limited success because they generated derivatives with much longer retention times than the original compounds [10]. Recently, the application of a novel technique based on the mass spectra of phenyl and cyclopentylimines has been used to characterize distributions of alkenones found in hypersaline sediments and coastal tidal ponds [1].However, the study of alkenone structures in samples from old sediments, e.g., those covering the last 250 k years of the history of the Mediterranean SST [6], showed that in some cases the sensitivity of the methods available [1] was not sufficient for the unambiguous determination of the position of the unsaturations because of the low concentrations of these compounds. Keeping in mind the previous experience with the use of C 5 amines, smaller molecular weight homologues with a lower boiling point were tested.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…However, attempts to locate the positions of the double bonds based on GC-MS studies of vicinal bistrimethylsilyl ethers [8] or dimethanethiols [9] had limited success because they generated derivatives with much longer retention times than the original compounds [10]. Recently, the application of a novel technique based on the mass spectra of phenyl and cyclopentylimines has been used to characterize distributions of alkenones found in hypersaline sediments and coastal tidal ponds [1].However, the study of alkenone structures in samples from old sediments, e.g., those covering the last 250 k years of the history of the Mediterranean SST [6], showed that in some cases the sensitivity of the methods available [1] was not sufficient for the unambiguous determination of the position of the unsaturations because of the low concentrations of these compounds. Keeping in mind the previous experience with the use of C 5 amines, smaller molecular weight homologues with a lower boiling point were tested.…”
mentioning
confidence: 99%
“…However, attempts to locate the positions of the double bonds based on GC-MS studies of vicinal bistrimethylsilyl ethers [8] or dimethanethiols [9] had limited success because they generated derivatives with much longer retention times than the original compounds [10]. Recently, the application of a novel technique based on the mass spectra of phenyl and cyclopentylimines has been used to characterize distributions of alkenones found in hypersaline sediments and coastal tidal ponds [1].…”
mentioning
confidence: 99%
See 3 more Smart Citations